ENGINEERING PROPERTIES TANAH LEMPUNG DENGAN SEMEN SEBAGAI SOIL IMPROVEMENT - Muthia Anggraini; Alfian Saleh; Virgo Trisep Haris (LPPM Universitas Abdurrab, 2024)
Volume instability in expansive soils due to changes in moisture content results in damage to the supporting structure. Soil improvement is one of the efforts made for soil improvement. Soil stabilization is one part of soil improvement. Appropriate soil improvement needs to be carried out to see the performance of the soil to meet post-construction stability requirements. Chemical stabilization using cementitious soil materials can improve the engineering properties of expansive soils. The research objective is to analyze the value of engineering properties of expansive soil with cement. Experimental research method to determine the value of California Bearing Ratio (CBR and Atterberg limits. Expansive soil was stabilized with cement with variations of 10, 12, and 14% cement by weight. As a result, the value of engineering properties increased, namely the maximum CBR value of 7.40% in the 14% variation at a curing time of 7 days. The smallest PI value in the 14% cement variation is 13.65%, there is a decrease in PI value with the addition of cement. In conclusion, engineering properties of soil with cement stabilization increase the CBR value of soil and decrease the Plasticity Index value.